2005
DOI: 10.1007/s10597-005-5004-z
|View full text |Cite
|
Sign up to set email alerts
|

Career Development in Schizophrenia: A Heuristic Framework

Abstract: Adults with schizophrenia continue to have poor rates of competitive employment. We have learned how to support individuals in the workplace with supported employment (SE); but have paid limited attention to early vocational identity development, work antecedents, illness characteristics, and career preferences. Vocational identity development is an important and natural condition of human growth for all persons and is well-researched in career counseling. For young adults with schizophrenia, the predictor of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 51 publications
1
24
0
5
Order By: Relevance
“…Young adults with psychosis perceive many barriers to employment—low self-confidence, stigma, symptom management, public benefits, goal ambiguity, and family members’ low expectations—yet they often remain motivated to seek employment in pursuit of financial stability, social inclusion, self-esteem, and a sense of normalcy (Boydell, Stasiulis, Volpe, & Gladstone, 2010; Rinaldi et al, 2010). Negative school and work experiences during pre-morbid/prodromal illness phases might diminish anticipated career outcomes and magnify perceived career barriers (Gioia, 2005). To inform the development of vocational services in early psychosis programs and affect lifelong workforce involvement, the field needs to learn more about how young adults with psychosis conceptualize the stages of career development through the telling of personal narratives.…”
mentioning
confidence: 99%
“…Young adults with psychosis perceive many barriers to employment—low self-confidence, stigma, symptom management, public benefits, goal ambiguity, and family members’ low expectations—yet they often remain motivated to seek employment in pursuit of financial stability, social inclusion, self-esteem, and a sense of normalcy (Boydell, Stasiulis, Volpe, & Gladstone, 2010; Rinaldi et al, 2010). Negative school and work experiences during pre-morbid/prodromal illness phases might diminish anticipated career outcomes and magnify perceived career barriers (Gioia, 2005). To inform the development of vocational services in early psychosis programs and affect lifelong workforce involvement, the field needs to learn more about how young adults with psychosis conceptualize the stages of career development through the telling of personal narratives.…”
mentioning
confidence: 99%
“…Estados Unidos e parte da Europa -como o Reino Unido e os países nórdicos (Gioia, 2005;Gove, 2004;Huffine & Clausen, 1979;Tsang et al, 2000;Weweiorski & Fabian, 2004)-, contudo ainda é um assunto incipiente em países como a Espanha (Crespo, 2007;Galilea & Colis, 2000;López et al, 2004;Mingote et al, 2008) e na América Latina (Favaro, 2006;Ribeiro, 1998Ribeiro, , 2001Ribeiro, , 2004Ribeiro, , 2006Ribeiro, , 2007Ribeiro, , 2009aRibeiro, , 2012Zambroni-de-Souza, 2006a, 2006b, 2006c. Além disso, o tema é basicamente estudado por autores de áreas especificamente dedicadas aos estudos da saúde, com algumas exceções, como Ribeiro (1998Ribeiro ( , 2001Ribeiro ( , 2004Ribeiro ( , 2006Ribeiro ( , 2007Ribeiro ( , 2009aRibeiro ( , 2012 El colectivo de personas con trastorno mental severo (…) parece caracterizarse, en general y muy especialmente en el terreno del acceso a la actividad productiva y el empleo, por una considerable complejidad y variabilidad sincrónica y diacrónica.…”
Section: Marcelo Afonso Ribeirounclassified
“…Outro ponto significativo de destaque são as pesquisas que apontam a real possibilidade de trabalho para as "pessoas vivendo com sofrimento mental" a despeito de todas as dificuldades encontradas (Álvarez, 2010;Burke-Miller et al, 2006;Ribeiro, 2009a), embora a maior parte desses estudos indique que o trabalho protegido ou apoiado seja a alternativa de maior sucesso (Ál-varez, 2010;Gioia, 2005;Tsang et al, 2000). Outrossim, apesar de a concepção de trabalho como tratamento (ergoterapia) ou de trabalho protegido ser uma etapa transitória importante para o (re) estabelecimento das articulações psicossociais entre trabalho e "loucura" (Álvarez, 2010;Gove, 2004;Tsang et al, 2000;Zambroni-de-Souza, 2006a), deve-se destacar que essas modalidades de trabalho podem contribuir para a cronicidade de uma situação de vulnerabilidade psicossocial, pois o trabalho, sempre que fosse possível, deveria ser "real, competitivo e remunerado, como potencial para o resgate da contratualidade psicossocial, entendida como habilidade de efetuar trocas em espaços concretos de ação entendidos como espaços públicos de interação" (Ribeiro, 2009a, p. 103).…”
Section: Marcelo Afonso Ribeirounclassified
See 1 more Smart Citation
“…Researchers have tended to focus on the individual's pathology, rather than the dynamics between the human, the work and the environment (Kirsh 2000a). Quite a few studies have revealed that the most consistent predictors of employment are recent work history, drive, self-efficacy (Gioia 2005;Marwaha and Johnson 2004;Rinaldi et al 2008;Bond et al 2001;Secker et al 2003;Catty et al 2008;Becker et al 2007).…”
Section: Introductionmentioning
confidence: 99%